COST-EFFECTIVENESS ANALYSIS OF ORGANIC HONEY PRODUCTION IN SERBIA - Nikolić, Marija; Nedić, Nebojša; Đorđević-Milošević, Suzana (Economics of Agriculture, 2022)
Economic justification of organic honey production is analyzed in the paper. The emphasis was placed on specific revenues and expenses that occur in organic honey production, and economic justification was examined by calculating indicators of economic efficiency, profitability and labour productivity. Based on the collected data, a calculation of production was made and a profitability threshold was established, which is achieved with 38 bee colonies, or with production volume of 570 kg of honey. Farms with more colonies have better indicators of production success. The expenses arising from the transition from conventional to organic production will be most quickly covered by farms with 200 bee colonies that generate enough income from organic honey production to operate positively in the third year of organizing such production.